Whole-Transcriptome Sequencing Identifies Key Differentially Expressed mRNAs, miRNAs, lncRNAs, and circRNAs Associated with CHOL - Kai-Jian Chu; Yu-Shui Ma; Xiao-Hui Jiang; Ting-Miao Wu; Zhi-Jun Wu; Zhi-Zhen Li; Jing-Han Wang; Qing-Xiang Gao; Bin Yi; Yi Shi; Hui-Min Wang; Li-Peng Gu; et al. (Elsevier, 2020)
To systematically evaluate the whole-transcriptome sequencing data of cholangiocarcinoma (CHOL) to gain more insights into the transcriptomic landscape and molecular mechanism of this cancer, we performed whole-transcriptome sequencing based on the tumorous (C) and their corresponding non-tumorous adjacent to the tumors (CP) from eight CHOL patients. Subsequently, differential expression analysis was performed on the C and CP groups, followed by functional interaction prediction analysis to investigate gene-regulatory circuits in CHOL. In addition, The Cancer Genome Atlas (TCGA) for CHOL data was used to validate the results. In total, 2,895 differentially expressed messenger RNAs (dif-mRNAs), 56 differentially expressed microRNAs (dif-miRNAs), 151 differentially expressed long non-coding RNAs (dif-lncRNAs), and 110 differentially expressed circular RNAs (dif-circRNAs) were found in CHOL samples compared with controls. Enrichment analysis on those differentially expressed genes (DEGs) related to miRNA, lncRNA, and circRNA also identified the function of spliceosome. The downregulated hsa-miR-144-3p were significantly enriched in the competing endogenous RNA (ceRNA) complex network, which also included 7 upregulated and 13 downregulated circRNAs, 7 upregulated lncRNAs, and 90 upregulated and 40 downregulated mRNAs. Moreover, most of the DEGs and a few of the miRNAs (such as hsa-miR-144-3p) were successfully validated by TCGA data. The genes involved in RNA splicing and protein degradation processes and miR-144-3p may play fundamental roles in the pathogenesis of CHOL.